2021
DOI: 10.1093/gbe/evab068
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal Inversion Polymorphisms in Two Sympatric Ascidian Lineages

Abstract: Chromosomal rearrangements can reduce fitness of heterozygotes and can thereby prevent gene flow. Therefore, such rearrangements can play a role in local adaptation and speciation. In particular, inversions are considered to be a major potential cause for chromosomal speciation. There are two closely related, partially sympatric lineages of ascidians in the genus Ciona, which we call type-A and type-B animals in the present study. While these invertebrate chordates are largely isolated reproductively, hybrids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…In two ascidians species of the genus Ciona and in insects like Drosophila inversions may promote speciation by reduction of the fitness or by causing sterility of heterozygotes. In the Anopheles gambiae species complex, inversions may allow for ecotypic differentiation and niche partitioning leading to different sympatric and genetically isolated populations ([13, 46, 54]). In groups like paserine birds where sexual differentiation is controlled by a ZW sex chromosome system (females being the heterogametic sex), inversions in the Z chromosome in particular seem to explain speciation in sympatry between close species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In two ascidians species of the genus Ciona and in insects like Drosophila inversions may promote speciation by reduction of the fitness or by causing sterility of heterozygotes. In the Anopheles gambiae species complex, inversions may allow for ecotypic differentiation and niche partitioning leading to different sympatric and genetically isolated populations ([13, 46, 54]). In groups like paserine birds where sexual differentiation is controlled by a ZW sex chromosome system (females being the heterogametic sex), inversions in the Z chromosome in particular seem to explain speciation in sympatry between close species.…”
Section: Discussionmentioning
confidence: 99%
“…Empirically and theoretically, it has been suggested that inversions may have contributed to speciation in sympatry in different groups of animals. In two ascidians species of the genus Ciona and in insects like Drosophila inversions may promote speciation by reduction of the fitness or by causing sterility of heterozygotes ( [60,61]). In the Anopheles gambiae species complex, inversions may allow for ecotypic differentiation and niche partitioning leading to different sympatric and genetically isolated populations [62].…”
Section: Structural Variations Between Genomes Of Sympatric Speciesmentioning
confidence: 99%
“…observed between P. brevispinus and P. ochraceus ( Fig. 3 ) represent assembly artifacts or evolved differences between species, the latter of which have been shown to lead to reproductive isolation and speciation in other marine invertebrate groups ( Satou et al 2021 ). Comparison of gene family duplication and loss can explain the evolution of complex traits ( Davidson et al 2020 ; Kenny et al 2020 ) and offers a useful strategy for testing genomic drivers of morphological and life history variation across sea stars.…”
Section: Discussionmentioning
confidence: 99%
“…89 orthologous Anoctamin protein sequences from 22 species ( Homo sapiens, Mus musculus, Xenopus tropicalis, Danio rerio, Petromyzon marinus, Eptatretus burgeri, Ciona intestinalis, Saccoglossus kowalevskii, Asterias rubens, Capitella teleta, Drosophila melanogaster, Oikopleura dioica, Branchiostoma floridae, Acyrthosiphon pisum, Strongylocentrotus purpuratus, Nematostella vectensis, Lottia gigantea, Caenorhabditis elegans, Aspergillus fumigatus, Nectria haematococca, Saccharomyces cerevisiae, Dictyostelium discoideum ), which were longer than 300 amino acids were downloaded from Uniprot 83 . 4 Ciona intestinalis Anoctamins were searched and download from Ciona genome database (Ghost 81 and Aniseed 80,84 ). Amino acid alignments were carried out by using the online version of MAFFT (https://www.ebi.ac.uk/Tools/msa/mafft/).…”
Section: Methodsmentioning
confidence: 99%
“…The primers for cloning C. intestinalis Ano10 cDNA were designed according to the Ciona intestinalis genome databases (Aniseed Database gene model KH2012:KH.C3.109; and Ghost Database KY21.Chr3.1036 80,81 ). A FLAG-tag sequence as DYKDDDDK was directly added to the primers for Ano10 cDNA amplification.…”
Section: Molecular Biology Procedures To Obtain Expression Constructs...mentioning
confidence: 99%